Model Pendidikan Keluarga Dalam Al-Quran Sebuah Kajian Kontemporer dalam Surat Al-Isra ayat 23-24 - Zamsiswaya; Nasrun Harahap (STAIN Bengkalis, 2023)
Education is considered the most influential effort in changing individual and societal behavior. Education is considered an effective social tool in shaping society in the future. Research reveals the Family Education Model in the Al-Quran, Study of Surah Al-Isra' (A Study in the Contemporary Era). For this reason, the main data that will be searched for are verses from the Al-Quran, especially in Surah Isra' which are relevant to the concept of family education. The primary data in this research is the Al-Qur'an. Primary data was obtained from verses from the Koran with the help of the books: Al-Mu'jam al-Mufahras li al-Faz al-Qur'an al-Karim, by Muhammad Fu'ad 'Abd al-Baqi. Based on the data analysis above, family education in the Al-Qur'an is to implement Amar ma'ruf nahi munkar. The family education model in Surah Al-Isra' in the Contemporary Era, namely the family education model has a general objective, namely a conscious and planned effort to create a learning atmosphere and learning process so that children actively develop their potential to have religious spiritual strength, self-control, personality, intelligence , noble morals, and skills needed by himself, society, nation and state. Meanwhile, the specific aim is that the family education model in the Al-Qur'an forms and builds perfect human beings physically and mentally, which is called al-insân al-kâmil which is based on the Al-Qur'an and hadith.